Student pharmacists' role in enhancing ambulatory care pharmacy practice - Lauren G. Pamulapati; Danielle Hess (Centro de Investigaciones y Publicaciones Farmaceuticas, 2020)
With a primary care physician shortage, utilization of pharmacists in the ambulatory care setting has proven to have positive economic and clinical outcomes for the practice and for patients. To extend the reach of the pharmacists, students may assist with patient care activities, such as medication reconciliation, point-of-care testing, and counseling. Evidence has shown that students benefit in building confidence, as well as improved perceptions of interprofessional care, while positive patient outcomes are maintained. There are many methods for schools to integrate these experiences early into their curriculum, as well as for students to explore opportunities on their own.